2015
DOI: 10.1002/ana.24427
|View full text |Cite
|
Sign up to set email alerts
|

Intelligence quotient improves after antiepileptic drug withdrawal following pediatric epilepsy surgery

Abstract: Start of AED withdrawal, number of AEDs reduced, and complete AED withdrawal were associated with improved postoperative IQ scores and gain in IQ, independent of other determinants of cognitive outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
96
2
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 111 publications
(111 citation statements)
references
References 24 publications
5
96
2
8
Order By: Relevance
“…In contrast to previous studies, IQ change in this cohort was not significantly influenced by postsurgical cessation of seizures or AED treatment . The more limited postsurgical use of topiramate in the current sample may account for differences in relation to other cohorts (eg, Skirrow et al).…”
Section: Discussioncontrasting
confidence: 95%
“…In contrast to previous studies, IQ change in this cohort was not significantly influenced by postsurgical cessation of seizures or AED treatment . The more limited postsurgical use of topiramate in the current sample may account for differences in relation to other cohorts (eg, Skirrow et al).…”
Section: Discussioncontrasting
confidence: 95%
“…[1][2][3][4] The decision to withdraw AEDs is partially based on an assessment of the risk of seizure recurrence. Being able to discontinue drugs is the ultimate proof of successful epilepsy surgery.…”
Section: Introductionmentioning
confidence: 99%
“…56 Studies in epilepsy surgery patients have demonstrated that AED withdrawal achieves incremental IQ gains. [58][59][60] In a recent, randomised, placebo-controlled, phase II, double-blind study in adolescents with uncontrolled focal-onset seizures (n=133), no statistically significant difference was reported for add-on perampanel versus placebo in Cognitive Drug Research global cognition score. 61 In this study, perampanel was increased weekly in 2-mg increments to 8-12 mg/day during 6-week titration and the maintenance phase lasted 13 weeks.…”
Section: Impact On Behavioural Change In Epilepsymentioning
confidence: 98%